Answer :
From the slope form of a line;
[tex] \frac{y-b}{x-a} =b[/tex]
y-b=bx-ab
y=bx-ab+b
y=bx-b(a-1)
[tex] \frac{y-b}{x-a} =b[/tex]
y-b=bx-ab
y=bx-ab+b
y=bx-b(a-1)
Answer:
The equation is y-a= b(x-b)
Step-by-step explanation:
I use bold for the slope so you can differentiate the slope term b from the y coordinate value b.
The equation of a line passing through a specific point and having a specific slope can be obtained using the point slope form of a line :
y-y1=m(x-x1) where m is the slope and (x1,y1) is your specific point.
So replacing your values, the point (x1,y1) =(a,b) and m=b, in this equation we havE:
y-a= b(x-b)
That can be expressed in point slope form and explicit for as.
y = b(x-b) + a = bx -bb +a =
y= bx + (a -bb)